Direct Comparison of Cardiac Troponin T and I Using a Uniform and a Sex-Specific Approach in the Detection of Functionally Relevant Coronary Artery Disease. (4th January 2020) - Mueller, Deborah; Puelacher, Christian; Honegger, Ursina; Walter, Joan E; Badertscher, Patrick; Schaerli, Nicolas; Strebel, Ivo; Twerenbold, Raphael; Boeddinghaus, Jasper; Nestelberger, Thomas; Hollenstein, Christina; du Fay de Lavallaz, Jeanne; et al.
Abstract: BACKGROUND: We aimed to directly compare high-sensitivity cardiac troponin I (hs-cTnI) and high-sensitivity cardiac troponin T (hs-cTnT) in the detection of functionally relevant coronary artery disease (fCAD). METHODS: Consecutive patients referred with clinical suspicion of fCAD and no structural heart disease other than coronary artery disease were included. The presence of fCAD was based on rest/stress myocardial perfusion single-photon emission computed tomography/computed tomography and coronary angiography. hs-cTnI and hs-cTnT concentrations were measured in a blinded fashion. Diagnostic accuracy was quantified using the area under the ROC curve (AUC) and evaluated both for uniform use in all patients and for sex-specific use in women and men separately. The prognostic end point was major adverse cardiac events (MACEs; cardiovascular death or myocardial infarction) within 2 years. For the prognostic performance, we used a multivariable model comparison with the Akaike information criterion (AIC). RESULTS: fCAD was detected in 613 of 2062 patients (29.7%) overall, 112 of 664 of women (16.9%), and 501 of 1398 of men (35.8%). hs-cTnI and hs-cTnT had comparable diagnostic accuracy when assessed for uniform use in all patients (AUC, 0.68 vs 0.66; P = 0.107) and separately in women (AUC, 0.68 vs 0.63; P = 0.068) and men (AUC, 0.65 vs 0.64; P = 0.475). However, women required lower rule-out cutoffs to achieve high sensitivity, and men needed higher rule-in cutoffs to achieve high specificity. hs-cTnI and hs-cTnT were strongly and independently associated with MACE within 2 years ( P < 0.001), with comparable prognostic accuracies by the AIC. CONCLUSIONS: hs-cTnI and hs-cTnT provide moderate and comparable diagnostic accuracy. Sex-specific cutoffs may be preferred. The prognostic utility of both troponins is comparable.